Coupling Bond Graph and Energetic Macroscopic Representation for Electric Vehicle Simulation - Silva, Luis Ignacio (2014)
This paper deals with the analysis and simulation of an electric vehicle, coupling functional and structural approaches in the same simulation environment. The Bond Graph model, the structural approach, is first deduced from the physical system, which in turn produces a direct correspondence between the system and its model. The control structure is then easily deduced from the Energetic Macroscopic Representation, the functional approach, of the vehicle using a systematic procedure. Simulation results are provided in order to analyze the performance of the closed-loop system.